2014
DOI: 10.1109/jbhi.2013.2282934
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Wireless Electrocardiogram Signal During Physical Exercise in Different Age Groups

Abstract: Electrocardiographic (ECG) recordings are usually obtained at rest. In many cases, real-time ECG monitoring in the home environment during daily life would be useful, but that requires a wireless device. The purpose of this paper is to evaluate the quality of the wireless ECG signals during physical activities. The test data were collected both in a normal exercise environment and in a radio frequency (RF)-shielded and noiseless environment. 30 test persons performed running, biking, or Nordic walking exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The ECG signal at position LS on the treadmill was acceptable in the range between 58.88 % and 62.18 %, and on the cycle ergometer signal was acceptable in the range between 75.92 % and 87.79 %. These results show significant improvement of the results presented in the study by Takalokastari et al [26], where it was shown that on the treadmill during running 60 % of the signal was of moderate or good quality, while on the cycle ergometer 73 % of the signal was of moderate or good quality. They reported that 79 % of the ECG signal on the treadmill was of moderate or good quality in the Nordic walking test.…”
Section: Discussionsupporting
confidence: 77%
“…The ECG signal at position LS on the treadmill was acceptable in the range between 58.88 % and 62.18 %, and on the cycle ergometer signal was acceptable in the range between 75.92 % and 87.79 %. These results show significant improvement of the results presented in the study by Takalokastari et al [26], where it was shown that on the treadmill during running 60 % of the signal was of moderate or good quality, while on the cycle ergometer 73 % of the signal was of moderate or good quality. They reported that 79 % of the ECG signal on the treadmill was of moderate or good quality in the Nordic walking test.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, a wireless EKG device was chosen to accommodate the motion inherent in the exercise protocol we employed. However, wireless EKG devices are inclined to have increased signaling noise as activity level increases, with increased errors seen during accelerated movements [31]. Although our EKG data were fairly noise-free, a small percentage of data were filtered out to decrease any motion-related artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The study, however, only reported arrhythmia classification results on 16 ECG recordings selected from the MIT-BIH arrhythmia database, and did not demonstrate the actual use of acceleration signals in the arrhythmia classification experiment. In [ 56 ], Takalokastari et al reported a significant correlation between noises in ECG signals and levels of acceleration signals based on an analysis of ECG and 3D acceleration signals acquired from 30 subjects during 3 types of ADLs, i.e. , running, biking, and walking.…”
Section: Related Workmentioning
confidence: 99%